PENERAPAN DISKRESI KEPOLISIAN DALAM PENANGANAN UNJUK RASA - Guntur Priyantoko (DE LEGA LATA: JURNAL ILMU HUKUM, 2016)
Basicly, demonstration is peace way to show opinion by mass, without unrest and under control but unfortunately it could be change anytime to be terrified condition because demonstrant do anarchy, such as throwing stone to house, office, and other strategic area so highest potential damages increase morevoer lives. It can’t be let so needed police officer to handle mass especially the demonstrant based on law. But the statute not always rules clearly about the police officer duty in facing demonstrant so that what police can be done is known as discretion. Discrestion application is done based on special procedure which is not defied the rule of law. .